EVALUASI IMPLEMENTASI PENJAMINAN MUTU PENDIDIKAN DI SMP NEGERI 2 BANYUKE HULU - Julia Larasanti; Radiana, Usman (UHN IGB Sugriwa Denpasar, 2024)
Quality of education is a major concern in many societies around the world. In the highly competitive education sector, the success of educational institutions depends on the quality of education. Education quality assurance is a systematic, integrated, and sustainable mechanism that ensures the entire process of organizing education meets quality standards. Quality assurance in basic education aims at the quality of education according to national education standards. This study aims to clearly describe quality assurance at the basic education level, especially junior secondary schools and equivalent. With the implementation of educational quality assurance, it is hoped that basic education can be properly implemented and evaluated.